Penyuluhan Kesehatan Tentang Stimulasi Dini Anak Usia 0-59 Bulan Pada Ibu-Ibu Posyandu Di Wilayah Kerja Puskesmas Rimbo Tengah Kab. Bungo - Suhaela Aro`fah; Erni Yuniati (LPPM AN Nuur, 2021)
Background: Children are the next generation of the Nation whose quality must be maintained, good or bad the quality of a child will depend on the quality of growth and development in the golden age, namely 0-5 years. .the main factor that affects the quality of children's growth and development is to stimulate children's development Purpose: Mothers are able to understand and carry out early stimulation independently of their children. Method: Provide health education about early stimulation. Results: Mothers who have followed.counseling is able to understand how to do early stimulation. Conclusion: All the material can be delivered well and can be accepted by the participants